2020
DOI: 10.3390/pharmaceutics12050446
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal and Ethosomal Gels for the Topical Delivery of Anthralin: Preparation, Comparative Evaluation and Clinical Assessment in Psoriatic Patients

Abstract: To enhance anthralin efficacy against psoriasis and reduce its notorious side effects, it was loaded into various liposomal and ethosomal preparations. The nanocarriers were characterized for drug encapsulation efficiency, size, morphology and compatibility between various components. Optimum formulations were dispersed in various gel bases and drug release kinetics were studied. Clinical efficacy and safety of liposomal and ethosomal Pluronic®F-127 gels were evaluated in patients having psoriasis (clinicaltri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 71 publications
2
57
0
Order By: Relevance
“…Minor shifting and reduced intensity of the characteristic peaks of AKBA may be attributable to the formation of hydrogen bonds, Van der Wall forces, or dipole interactions between AKBA and other excipients increasing both the encapsulation of AKBA and the stability of the nano-vesicles. 38 These findings are in accordance with Fathalla et al 75 who reported the absence of interactions between the drug and other ingredients of the Anthralin-loaded ethosomal formulations according to the FTIR spectrum that displayed the characteristic peaks of both drug and ‎excipients with a little shift.…”
Section: Resultssupporting
confidence: 88%
“…Minor shifting and reduced intensity of the characteristic peaks of AKBA may be attributable to the formation of hydrogen bonds, Van der Wall forces, or dipole interactions between AKBA and other excipients increasing both the encapsulation of AKBA and the stability of the nano-vesicles. 38 These findings are in accordance with Fathalla et al 75 who reported the absence of interactions between the drug and other ingredients of the Anthralin-loaded ethosomal formulations according to the FTIR spectrum that displayed the characteristic peaks of both drug and ‎excipients with a little shift.…”
Section: Resultssupporting
confidence: 88%
“…Definitely, this indicated synergistic effect of ethanol on the drug permeation across the skin, which could be returned to its effective role as a penetration enhancer [ 33 ]. In addition to the lipid-softening effect of ethanol that facilitate the penetration of the drug and improve the permeation as well [ 34 ]. In view of this, the skin permeation is affected by varying the concentration of phospholipid and ethanol [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is a commonly observed behavior for nanoparticles due to the dry status of nanoparticles used in TEM measurements, which probably results in nanoparticle shrinkage. In contrast, the size obtained by DLS represents hydrated nanoparticles in solution, which explains their bigger size [35,36].…”
Section: Preparation Of Egcg-gnpsmentioning
confidence: 91%
“…Furthermore, the potential of a given nanocarrier clinical translation is higher for those having high drug loading capacity since this minimizes the concentration of nanocarrier needed to achieve a clinically relevant drug concentration. A lower nanocarrier concentration not only limits the burden on the body to metabolize and excrete these chemicals, but also improves the colloidal stability of nanocarriers [35,48].…”
Section: Effect Of Egcg/haucl 4 Molar Ratio On Drug Loading Propertiesmentioning
confidence: 99%